The Technology of Interactive Compilation - Evangelatos, Timothy V. (The International Hydrographic Review, 2015)
Digital technology now makes it possible to compile a nautical chart from digital source data, and to draft the chart automatically. This paper describes some of the hardware and software tools used in the Canadian Hydrographic Service that make this process possible. It also considers what has to be done to make these techniques more effective, how the technology is expected to evolve, and the impact of these changes on chart producing organizations.